Penggunaan Teknik Time Token Arends Pada Metode Debat Untuk Meningkatkan Kemampuan Memproses Informasi Siswa Dalam Pembelajaran Sejarah - Ayu Oktapiani; Murdiyah Winarti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2019)
The article entitled Time Token Arends Implementation in the Debate Method to Improve the Student Information Processing Skill in History Study. The background of this research was the lack of students’ information processing skill, where students often had difficulties on remembering the material easily, the lack of distribution and participation in communicating their opinion and argument as the result of information processing and becomes the characteristic of the passive class. The purpose of this study is to improve students’ information processing skill. Began with the identification, implementation, improvement and obstacles during the conducted ofthis research and the effort that implemented to resolve those obstacles. The research design used Kemmis and Mc. Taggart classroom action research model. Data collection that used is observation, interview and documentation study. Data collection tools or research instrument that used field note, teacher and student guidance observation paper and interview guidance. This research consists of three cycles and three actions. The observation result of each cycle that increased significantly from the first cycle until the third cycle. Some of the recommendation to the teacher, school, otherresearchers and History Education Department, which are the facilities optimization and communication tools in school.